Signal processing of GPS radio shadows formed by moving targets - Kabakchiev, Chr; Garvanov, I.; Behar, V.; Kabakchieva, D.; Kabakchiev, K.; Rohling, H.; Kulpa, K.; Yarovoy, A. (2015 Signal Processing Symposium (SPSympo), 2015)
This paper focuses on scientific issues related to new application of GPS in the construction and development of radar networks using the effect of Forward Scatter (FS) of electromagnetic waves for detection of objects by using of their GPS radio shadows. The paper theme is new, it combines two thematic areas: processing of GPS signals and processing of radar signals in FS radar systems.